VALIDATED SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF MONTELUKAST SODIUM IN PURE AND DOSAGE FORMS USING N-BROMOSUCCINIMIDE AND DYES - EL-SHEIKH, RAGAA; HASSAN, WAFAA S.; FAHMY, Rowaida; GOUDA, AYMAN A. (International Journal of Applied Pharmaceutics, 2020)
Objective: Simple, sensitive, precise, reproducible and validated spectrophotometric methods have been developed for the quantification of montelukast sodium as leukotriene receptor antagonist drug, in pure and dosage forms (tablets). Methods: The methods use N-bromosuccinimide (NBS) as an oxidant and three dyes, amaranth, methylene blue, and indigo carmine, as auxiliary reagents. The three methods are based on oxidation reaction of montelukast sodium with a known excess of N-bromosuccinimide (NBS) in acid medium, followed by determination of unreacted NBS by the reaction with a fixed amount of dyes, amaranth, methylene blue, and indigo carmine followed by the measurement of the absorbance at 520, 664 and 610 nm, respectively. Results: Under the optimum conditions, linear relationships with good correlation coefficients (0.9993-0.9996) were found over the concentration ranges of 0.5-10, 1.0-12 and 0.5-8.0 µg/ml with a limit of detection (LOD) of 0.15, 0.3 and 0.14 µg/ml using amaranth, methylene blue, and indigo carmine methods, respectively. Intra-day and inter-day accuracy and precision of the methods have been evaluated. No interference was observed from the common tablet excipients. Conclusion: The proposed methods were validated in accordance with ICH guidelines and successfully applied to the analysis of montelukast sodium in dosage forms (tablets). The reliability of the methods was further ascertained by performing recovery studies using the standard addition method. Statistical comparison of the results obtained by applying the proposed methods with those of the reported method by applying student’s t-test and F-test revealed good agreement.